Penerapan Arsitektur High-Tech Pada Perancangan Gelanggang Olahraga Di Pondok Jaya, Pondok Aren, Tangerang Selatan, Banten - Anggito Abimanyu Nadjib; Harfa Iskandaria; Tri Endangsih (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2022)
Abstract A Sports Arena is a large enclosed platform, often circular or oval in shape, designed for theatrical performances, musical performances, or sporting events. The sports arena is used as a means of performance or sports center training for national athletes and novice athletes who just want to enter the realm of professional sports. The construction of the Sports Center uses the HIGH-TECH concept, very suitable for use in designs in the South Tangerang City area, with its elegant design depicting a modern spirit and technology that is displayed in the form of structural honesty, color play, the use of the latest technology in building structures, and has some uniqueness. so that this High-Tech feature is not the same as other characteristics and can make an area a building icon that is recognized by many people. Keyword : Sports Center, international standard, High-Tech Architecture